UNDERSTANDING THE FRACTIONAL RESERVE BANKING SYSTEM - Lazizbek Nurmuhammadov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
The Fractional Reserve Banking System is a foundational element of modern finance that is pivotal in money creation, economic growth, and financial stability. This article provides a concise overview of the fractional reserve banking system, outlining its history, key principles, and positive and negative aspects for the financial industry and the economy.